Management of multiple trichoepithelioma: A review of pharmacological therapies. (5th January 2021) - Lobo, Yolanka; Blake, Tristan; Wheller, Laura
Abstract: Trichoepithelioma is a rare benign adnexal neoplasm that can occur in various forms including solitary, multiple, familial or nonfamilial. Multiple facial trichoepithelioma can be associated with significant psychosocial burden. Conventional treatment modalities such as surgical excision and ablative laser have variable results and can be associated with unacceptable complications and tumour regrowth. Pharmacological interventions such as topical and systemic agents are potentially effective but clinical data are limited and treatments are poorly standardised. We review the available evidence to determine the role of pharmacological therapies in the management of multiple trichoepithelioma. Demographic and clinical data were retrospectively collected from the available English literature. Majority of cases treated with pharmacological therapies (93.75%) had a positive treatment outcome, achieving partial lesion response. Adverse effects associated with pharmacological therapies were generally well tolerated and did not interrupt treatment. There are limitations as to how our results can be interpreted owing to the paucity of good quality evidence, spectrum of disease severity, and diversity of study designs utilised in the included articles. Nonetheless, the results of our study indicate that while most pharmacological interventions for multiple trichoepithelioma produce a partial response, they can be employed as effective suppressive therapies, either alone or in conjunction with conventional treatments. The current evidence for pharmacological therapies remains largely anecdotal justifying the need for further clinical studies in this area.